Mapping the maternal vaccination journey and influencing factors for Māori women in Aotearoa New Zealand: a qualitative study - Cameron C. Grant; Helen Petousis-Harris; Felicity Dumble; Owen (Te Rarawa); Samuel (Nga Puhi); Natalie Gauld (CSIRO Publishing, 2022)
Introduction Uptake of maternal vaccinations (MVs) is suboptimal in Aotearoa New Zealand, particularly for Māori. Aim To describe Māori women's journeys regarding maternal pertussis and influenza vaccinations and explore influences on uptake. Methods Semi-structured interviews were conducted in Waikato, Aotearoa New Zealand, with pregnant or recently pregnant Māori women, and separately with Māori healthcare professionals (HCPs) to understand women's decisions regarding MVs and enablers and barriers to uptake. Results Nine women and nine HCPs were interviewed. Verbal communications from midwives, general practice and pharmacy strongly influenced women's journeys. Women's decisions appeared largely straight-forward, with influences including awareness, knowledge, underlying beliefs and previous MVs. Enablers for MV uptake included HCPs' discussions, pro-vaccination beliefs, and accessibility. Barriers for MV uptake included poverty (and transport), lack of awareness, insufficient knowledge of benefits, late presentation to the midwife and other commitments or challenges in the women's lives affecting prioritisation of the vaccine. Misconceptions, seasonality, and lower HCP emphasis impaired influenza vaccination uptake. Discussion With multiple barriers to accessing MVs, HCPs who see pregnant women are the primary resource to improve awareness, knowledge, and access through kōrero (discussions) with the woman and, where possible, being able to administer the vaccinations. These HCPs need to be well-informed, aware of likely concerns women may have and how to address them, encourage these discussions and preferably be trusted.